Binary Thinking and the Limiting of Human Potential. (2nd November 2021) - Shelton, Jama; Dodd, S. J.
Abstract: Our society compresses a multitude of human identities into arbitrary categories, many of which are constructed as binaries. Binary constructs offer two mutually exclusive, possible ways of being. Perhaps the most prevalent in US society is the gender binary – the pervasive idea that there are two, rigidly boundaried gender categories, each with an accompanying set of expectations. Binary gender classifications are a foundational element of US social structures that foreclose possibilities for who individuals are and who they can become. Binaries create a hierarchy within which one category is "better" than the other. This hierarchical order is embedded in societal structures and tightly bound with systems of oppression, confirming power and privilege and maintaining a social order rooted in racism, sexism, heterosexism, and cisgenderism. Not only is the maintenance of this social order limiting, it also perpetuates violence and marginalization. This paper examines the ways in which the gender binary produces and maintains the violence against and marginalization of transgender and nonbinary people. It concludes with recommendations for moving beyond binary thinking, particularly within the public sector, in order to create systems and institutions that better support human potential and open possibilities for all people.